The Effect of Drilling Training Methods on Shooting Results in Extracurricular Football at SMAN 1 Kalijati - Dapit Hidayat; Rhama Nurmansyah; Citra Resita (STKIP Muhammadiyah Kuningan, 2022)
This study aims to determine the effect of the drilling method on the shooting results in extracurricular football at the State High School 1 Kalijati. This study uses a quantitative approach. If viewed from the type of data presented, the method in this study is an experimental study. The sample used is a total sampling of 30 students. The results of the research on the effect of the drilling method on the shooting results in extracurricular football at the State High School 1 Kalijati obtained a minimum pretest value of 1, a maximum of 12 and a mean of 5.13 and a Standard Deviation of 3.213, while for the posttest the minimum value of 3 was obtained, a maximum of 15 and the mean is 8.33 with a Standard Deviation of 3.021. Based on the results of calculations with data processing research results, it can be concluded that the drilling method on the shooting results in football extracurriculars at SMAN 1 Kalijati has an effect.